Application of a kiln drying technique to Quercus suber L. cork planks - Carpintero, E.; Jurado, M.; Prades, C. (Food and Bioproducts Processing, 2014)
At present, all of the cork used to manufacture natural stoppers is air dried for a minimum of 6 months. This study evaluates the feasibility of applying a kiln drying technique to cork planks. We used a sample of 65 planks, each of which was divided into two pieces. One sub-set of planks was air dried for 6 months following the traditional procedure, while the other was kiln dried for 14 days. The evolution of moisture content was controlled, and both methods were compared by means of a statistical analysis of the thickness, quality, porosity coefficient, color and compressive properties of the cork. The reduction in moisture content was similar for both traditional air drying and kiln drying. At the end of the drying, cork thickness increased with both methods, although a larger increase was observed for the kiln drying method. Statistically significant differences were not found for the mean porosity coefficient or quality. Although statistically significant differences in the color of the cork were detected, it would be necessary to verify if such differences are detectable by the human eye. No differences were found in the compressive properties of the cork for a significance level of less than 1%. This feasibility study concludes that kiln drying is a suitable technique as it significantly reduces the drying time and holding costs of the raw material. The application of this technique would constitute an innovation in the transformation process by controlling the climatic variables that affect the drying process.
Keywords: Compressive properties; Kiln drying; Moisture content; Quality; Thickness; Traditional air drying

Drying kinetics of cork planks in a cork pile in the field - Costa, Augusta; Pereira, Helena (Food and Bioproducts Processing, 2012)
Moisture content is one important parameter in the trading of raw cork planks after harvesting. This study presents a mathematical modeling of the drying curve of raw cork planks in a cork pile in the ﬁeld, under natural sun drying conditions. Experimental data were obtained by following the water loss (i.e. by daily weighing) of 97 cork planks positioned in nine points within a cork pile. Immediately after harvesting, the raw cork planks had a mean moisture content in a dry basis of 40.4% and after 20-day drying 16.6%. The drying process of the cork planks showed three phases: drying was very fast in the ﬁrst 2 days; in the next 2–15 days there was a decreasing drying rate; and a ﬁnal phase, after 15 days in the cork pile, with a slightly decreasing drying rate. Mathematical modeling provided a direct relation between moisture content and drying time. After comparing sixteen empirical drying models, the Modiﬁed Henderson and Pabis model showed the best ﬁt. According to this model, the cork planks are commercial dry (14% moisture content in a wet basis) 15 days after harvest.
The following values have no corresponding Zotero field: publisher: Institution of Chemical Engineers
Keywords: Cork; empirical drying models; Moisture content; moisture ratio; natural sun drying

Effect of different storage conditions in recalcitrant seeds of holm oak (Quercus ilex L.) during germination - Pasquini, S; Braidot, E; Petrussa, E; Vianello, A (Seed Science and Technology, 2011)
The effect of three different storage treatments on holm oak (Quercus ilex L.) acorns was examined over a period of twelve months. Acorns from two seed lots were stored at 3°C with three different treatments: acorns mixed with peat inside a can with a pierced pipe through the middle, acorns mixed in moistened sand, or acorns inside polyethylene bags without medium. Samples were collected every two months and were analyzed for moisture content, germination and electrolyte leakage. Storage of acorns in polyethylene bags maintained the high seedling percentage usually observed after harvest in germination tests. The acorns stored mixed with peat or sand failed to maintain the germination vigour observed at harvest. Electrolyte leakage was significantly higher for acorns stored in peat rather than for the other two treatments. However, acorns stored in sand and in peat had a higher level of moisture content than those kept in polyethylene bags. These results suggest that storage of acorns from the recalcitrant holm oak in polyethylene bags could preserve the acorn germination over a longer period of time with respect to the usual methods.
Keywords: acorn storage conditions; electrolyte leakage; germination; Holm oak; Moisture content; recalcitrant seed (voyant)

A Simple Technique to Estimate the Flammability Index of Moroccan Forest Fuels - Hachmi, M'Hamed; Sesbou, Abdessadek; Benjelloun, Hassan; El Handouz, Nesrine; Bouanane, Fadoua (Journal of Combustion, 2011)
A formula to estimate forest fuel flammability index (FI) is proposed, integrating three species flammability parameters: time to ignition, time of combustion, and flame height. Thirty-one (31)Moroccan tree and shrub species were tested within a wide range of fuel moisture contents. Six species flammability classes were identified. An ANOVA of the FI-values was performed and analyzed using four different sample sizes of 12, 24, 36, and 50 flammability tests. Fuel humidity content is inversely correlated to the FI-value, and the linear model appears to be the most adequate equation that may predict the hypothetical threshold-point of humidity of extinction. Most of the Moroccan forest fuels studied are classified as moderately flammable to flammable species based on their average humidity content, calculated for the summer period from July to September.
Keywords: flammability; forest species; Moisture content; Morocco (voyant)

Comportement physiologique des glands de chêne liège (Quercus suber L.) durant leur conservation et variabilité inter-individus producteurs - Merouani, Hachemi; Branco, Carmen; Almeida, Maria Helena; Pereira, João S (Ann. For. Sci., 2001)
The mature acorns were harvested on twelve selected trees from a cork oak population in Southern Portugal (Herdade da Palma). After drying, the seed lots were stored on three types bags (polyethylene with 30 mm and 50 mm thick and plastic mesh), for six months at 0 oC. At the time of natural dissemination, the acorns from the majority of the trees from the same population were under the same state of morphological and physiological maturity. The moisture content was about 44-47% and a germination rate above 92% . At this time, the germination was very slow because of the existent embryonic dormancy that seems to be dependent on the individual trees. During the storage, germination rate is improved. This might be explained by the breaking dormancy during storage. The mean germination time was on an average 10 days for fresh seeds and decreased to about 4 days after 6 months storage. A relationship between viability and seed moisture content was observed. The Mean Germination Time of dried seed and stored seed for 4 months in plastic mesh bag increased to about 13 days. The germination capacity was strongly decreased when the seed moisture content was below 30%
Keywords: electrolyte leakage; germination; Moisture content; Quercus suber; seed; storage

Comportement physiologique des glands de chêne liège (Quercus suber L.) durant leur conservation et variabilité inter-individus producteurs - Merouani, Hachemi; Branco, Carmen; Almeida, Maria Helena; Pereira, João S. (Ann. For. Sci., 2001)
The mature acorns were harvested on twelve selected trees from a cork oak population in Southern Portugal (Herdade da Palma). After drying, the seed lots were stored on three types bags (polyethylene with 30 mm and 50 mm thick and plastic mesh), for six months at 0 oC. At the time of natural dissemination, the acorns from the majority of the trees from the same population were under the same state of morphological and physiological maturity. The moisture content was about 44-47% and a germination rate above 92% . At this time, the germination was very slow because of the existent embryonic dormancy that seems to be dependent on the individual trees. During the storage, germination rate is improved. This might be explained by the breaking dormancy during storage. The mean germination time was on an average 10 days for fresh seeds and decreased to about 4 days after 6 months storage. A relationship between viability and seed moisture content was observed. The Mean Germination Time of dried seed and stored seed for 4 months in plastic mesh bag increased to about 13 days. The germination capacity was strongly decreased when the seed moisture content was below 30%
Keywords: electrolyte leakage; germination; Moisture content; Quercus suber; seed; storage

Cork hygroscopic equilibrium moisture content - Gil, L; Cortiço, P (European Journal of Wood and Wood Products, 1998)
This work is related to the establishment of the curves of cork moisture content in hygroscopic equilibrium (HEM curves), which allow to predict the moisture content of cork planks, one of the most important parameters in cork trading and processing. HEM curves for 20 ~ and 40 ~ based on an empirical model related to experimental data, were mathematically treated in order to set a series of curves in steps of 5 ~ These curves were transformed in a more usual display of the hygroscopic equilibrium mois- ture content, for the most common temperature and hu- midity ranges and tested against experimental data using two cork types.
Keywords: Cork; HEM curves (voyant); Moisture content; weight

CHARACTERIZATION OF WETCORK IN QUERCUS-SUBER L - PARAMESWARAN, N; LIESE, W; GUNZERODT, H (HOLZFORSCHUNG, 1981)
The wetcork containing more than 400% moisture is developed as islets in the otherwise dry cork tissue of Quercus suber. A characterization using electron moscroscopy yielded no marked differences in the wall structure, except for formation of gaps due to lack of substances in the middle lamella of some wetcork cells. The chemical constitution of the two tissues types equally showed no obvious differences. During drying the wetcork shrinks to a great extent, thus influencing the utilization of such a cork in certain fields of application.
Keywords: chemical constitutions; Fine structure; Moisture content; Quercus suber; shrinkage; utilization; wetcork